Efektivitas Project Based Learning dalam Meningkatkan Kompetensi Siswa pada Pelajaran Instalasi Penerangan Listrik - Anisa Fitri; Usmeldi Usmeldi (Jurnal Pendidikan Teknik Elektro, 2022)
This research aims to determine the effectiveness of the Project Based Learning learning model to improve the competence of class XI TITL students at SMK Muhammadiyah 1 Padang. Student learning outcomes are still low caused by the factor of the learning model that is still teacher-centered, thus affecting the cognitive and psychomotor domains of students. Therefore, it is necessary to conduct research with the application of Project Based Learning to see the effectiveness of student competence. This study uses an experimental research type which is categorized into a quasi-experimental type of research with a one group pretest posttest design. The subjects of this study were students of class XI TITL SMK Muhammadiyah 1 Padang in the academic year 2022/2023 which consisted of 16 students. To measure this effectiveness, a pretest was given before the implementation of Project Based Learning in learning. Posttest is given after the learning process of Electrical Lighting Installation. The posttest results will be analyzed using a series of tests such as classical completeness and effect size. The test results show that the value of students who applied Project Based Learning was better than students who did not apply Project Based Learning. Student learning outcomes after implementing Project Based Learning increased. So that Project Based Learning is effective to improve student competence.